Targeting Gelatinases with a Near-Infrared Fluorescent Cyclic His-Try-Gly-Phe Peptide - Wang, Wei (2009)
PURPOSE: To synthesize and characterize near-infrared (NIR) fluorescence imaging probes targeted to gelatinases. PROCEDURES: A phage display-selected cyclic peptide containing the His-Try-Gly-Phe (HWGF) motif was used as the lead compound. Structure-activity relationship analysis was used to identify stable and potent gelatinase inhibitors suitable for NIR imaging applications. RESULTS: Replacing the S-S bond in cyclic peptide c(CTTHWGFTLC)NH(2) (C1) with an amide bond between the ε-amino group of Lys and the side chain of Asp resulted in a significant increase in stability and a 4-fold increase in gelatinase inhibition of the resulting peptide, c(KAHWGFTLD)NH(2) (C6). Conjugation of Cy5.5 to C6 led to Cy5.5-C6, which was selectively taken up by MMP-2 expressing human glioma U87 cells. In vivo, selective accumulation of Cy5.5-C6, but not Cy5.5-C1 or a Cy5.5-scrambled peptide conjugate, was visualized in intratibial prostate PC-3 tumors 48 hr after their intravenous injection. Moreover, Cy5.5-C6 was readily visualized in orthotopically inoculated U87 brain tumors. CONCLUSIONS: Cy5.5-C6 may be a useful agent for molecular imaging of gelatinases. The approach of producing stable cyclic peptides through side chain amide linkage should be applicable to other peptide-based imaging agents.